2022
DOI: 10.3390/ijerph19074115
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Prenatal Breastfeeding Self-Efficacy in Expectant Mothers with Gestational Diabetes Mellitus

Abstract: Breastfeeding is beneficial for mothers with gestational diabetes mellitus (GDM). Saudi Arabia is considered one of the countries with the highest prevalence of GDM. Mothers with GDM have a low intention to breastfeed and are less likely to continue breastfeeding. This study aimed to measure breastfeeding self-efficacy among expectant mothers with GDM and quantify its determinants. This cross-sectional study recruited expectant mothers with GDM from an antenatal care clinic and queried them on breastfeeding kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The present study found that adequate breastfeeding knowledge and positive attitudes predict higher BSE. At a national level, a recent Saudi study showed that mothers with gestational diabetes mellitus who had good breastfeeding knowledge were more likely to have higher BSE [33]. The significant role of knowledge in the current study indicates the importance of promoting strategies to improve nursing mothers' breastfeeding awareness and self-efficacy.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The present study found that adequate breastfeeding knowledge and positive attitudes predict higher BSE. At a national level, a recent Saudi study showed that mothers with gestational diabetes mellitus who had good breastfeeding knowledge were more likely to have higher BSE [33]. The significant role of knowledge in the current study indicates the importance of promoting strategies to improve nursing mothers' breastfeeding awareness and self-efficacy.…”
Section: Discussionmentioning
confidence: 59%
“…A high educational level may enhance BSE, empowering the mother in terms of health-seeking behavior and health education. Prior studies emphasized the important role of a high educational level in raising women's BSE and consequently enhancing successful breastfeeding practices [33,34]. In addition, cross-sectional surveys conducted in Taiwan suggested that educational level was positively associated with an increased likelihood of BSE, particularly among university-educated mothers [35].…”
Section: Discussionmentioning
confidence: 99%
“…The first section asked about social and demographic characteristics, while the second section asked about obstetrics, antenatal, perinatal, and postnatal history. These two sections were constructed by the investigators based on a literature review and the ten steps of the WHO's Baby Friendly Hospital Initiative (BFHI) [6,[8][9][10][11]14,15,29,30]. The third section asked about the exposure to counseling types and frequency (the exposure of interest), which is based on the WHO's 2018 guidelines on breastfeeding counseling [16] and McFadden et al's systemic review and meta-analysis [13].…”
Section: Data Collection Toolmentioning
confidence: 99%
“…They also need it for professional medical advice in situations such as mastitis and feeding a premature infant, as well as psychological support. Previous studies in Saudi Arabia have focused only on the one-way health education aspect of breastfeeding counseling [8,11,12,14,15].…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 1 more Smart Citation